VISUALIZING HISTORY: THE ‘SOVIET KAZAKHSTAN’ NEWSREEL SERIES - Clarke, John; Seksenbayeva, G. (Journal of history, 2018)
This article investigates the emergence, development and role of the newsreel during the Soviet period of Kazakh history. In particular, it focuses on the ‘Soviet Kazakhstan’ series, which was produced over six decades. The article stresses the value of the newsreel as an historical source, one relatively neglected in the past. It explores the reasons why the new Communist authorities were attracted to the newsreel, a mass medium that could play a central role in the building of a socialist society. It goes on to consider the relationship between the ‘message’ of newsreels and the ideological stance of the Communist party – and particularly on those occasions when the two were literally ‘out of sync’. The article also investigates the subject matter of newsreels produced in the 1930s and 40s and the extent and nature of Party control. It discuss the changes of the 1960s, changes that allowed for a greater emphasis on character in addition to the simple portrayal of events. It argues, however, that these changes were modest and that, even in the 1980s, the predominant images were of factories and combine harvesters. It concludes that the newsreel played a central role in promoting acceptance of the principles of Communism and, perhaps more prosaically, in raising hopes of a better future. While accepting that ‘Soviet Kazakhstan’ was always ideologically conditioned, the article contends that it did create an invaluable screen chronicle that reflected at least some aspects of reality.